Tourist attitudes toward the use of e-Commerce for tourism in Thailand - Suanpang, Pannee (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The aim of this paper is to study travelersâ€™ attitudes toward the use of e-Commerce for tourism in Thailand. The study used mixed methodology quantitative research by collecting data from 510 domestic tourists; 400 international tourists and used qualitative research by collecting data from in-depth interviews.Â  The result found that domestic tourists use e-Commerce at a higher level than international tourists for booking hotels, tours, transportation and for buying souvenirs; however, international tourists use e-Commerce at a higher level than domestic tourists for booking at restaurants. The payment method found that domestic tourists pay in cash, do bank transfers and do mobile payments at a higher level than international tourists, but international tourists pay by credit card and use counter services more than domestic tourists. The result of the statistics test in order to compare tourism e-Commerce system needs shows that there is significant difference between the attractiveness of websites; updated information; credit card security system and product and service items. The result of the statistics test concerning the comparison of traveler attitudes towards the use of e-commerce for tourism shows the most significant differences in generating fast and effective communication: e-Commerce can produce product reliability; has a safe payment system; has safe information privacy; can develop good image of product and services and can create product and service identification.